(untitled) (Global Scientific Review, 2025)
This article explains the meaning of the concept of digitalization. The main characteristic of modern information processes is visual practice, which becomes the basis of everyday life. Today, people, even schoolchildren, are distinguished by the fact that they receive and perceive more and more information through the “screen”. The field of education is explored by studying, systematizing and generalizing the existing practice of obtaining scientifically based conclusions on the introduction of digital technologies in education